Similarities and Differences between River Buffaloes and Cattle: Health, Physiological, Behavioral and Productivity Aspects - Bertoni, Aldo; Napolitano, Fabio; Mota-Rojas, Daniel; Sabia, Emilio; Álvarez-Macías, Adolfo; Mora-Medina, Patricia; Morales-Canela, Armando; Berdugo-Gutiérrez, Jesús; Guerrero- Legarreta, Isabel (Journal of Buffalo Science, 2020)
The river buffalo is an emerging production species worldwide; indeed, it is overtaking other cattle as a producer of meat and milk in some countries. Though both species belong to the Bovidae family, they show significant anatomical, physiological, and behavioral differences due to their different phylogenetic positions. The river buffalo is a rustic animal that can benefit from low-quality, fibrous forages due to its digestive system, in contrast to beef cattle or dairy cows. Besides, the buffalo cow’s reproductive apparatus has fewer cervical muscle rings and a shorter vagina and cervix. This species has maintained its seasonal breeding pattern, also in contrast to Bos indicus and Bos taurus. Even though buffaloes have an inefficient thermoregulating system, scarce hair, and a thicker epidermis, they are more resistant to tropical weather conditions if water for wallowing is available than dairy cows, which in turn adapt better to temperate zones. Due to the morphology of the river buffalo’s mammary glands, they produce less milk, while their conical teats with narrower sphincters decrease predisposition to mastitis compared to dairy cows. Thus, the study of the anatomical and physiological differences among river buffalo, Bos Taurus, and Bos Indicus will allow the implementation of strategies to improve the former’s productivity while also increasing welfare levels according to the production system in which they are raised.